(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
This study examines plant-soil interactions involving zinc (Zn), focusing on the physiological effects on plant development and the molecular interactions between plant proteins and metal ions. About 2 kg of soil mixed with gravel (1.5:1 v/v) were placed in pots, and seeds of sunflower (Helianthus annuus), amaranth (Amaranthus spp.), cowpea (Vigna unguiculata), and groundnut (Arachis hypogaea) were sown and irrigated for two weeks. Seedlings were treated with a 500 ppm zinc sulfate solution, and shoots, leaves, and roots were separated for length and weight measurements. Zinc concentration in digested tissues was determined using atomic absorption spectroscopy (AAS). Computational modeling and molecular docking were performed using PubChem data and structural tools such as Chimera, Phyre2, and PyMOL. The BbZIP protein structure was modeled, and active sites were predicted using COACH-D, while CAVER Web 1.0 identified quantum tunnel pathways. Phytochemical analysis revealed the presence of bioactive compounds, including flavonoids, tannins, steroids, and saponins. Treated plants exhibited reduced growth compared to the controls, with significant zinc accumulation in the soil, shoots, and roots. The highest Zn concentration (315 ppm) occurred in groundnut roots. Five major binding poses were identified, involving catalytic residues Met91, Leu92, Phe94, Ala95, Ala96, Pro210, Glu211, Ala214, Gly93, and others. Molecular docking showed a binding affinity of –3.8 kcal/mol and an inhibition constant (Ki) of 247.81 mM. The BbZIP–Zn complex was stabilized by four hydrogen bonds (Ala96, Ala290, Ser236, Leu294). Overall, this study highlights the critical role of zinc in plant stress responses and development through physiological and molecular mechanisms.